1998
DOI: 10.1002/(sici)1097-0215(19980619)79:3<288::aid-ijc14>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of colorectal cancer cells in peripheral blood by reverse-transcriptase polymerase chain reaction for cytokeratin 20

Abstract: The staging of colorectal cancer currently depends on pathological examination of the surgical specimen and regional lymph nodes, accompanied by imaging tests such as computed tomography (CT) scanning. However, alternative molecular methods to detect circulating tumour cells in blood or bone marrow may provide additional information about the extent of disease and prognosis. We have previously reported the development of a reverse‐transcriptase polymerase chain reaction (RT‐PCR) for cytokeratin 20 (CK 20) mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(30 citation statements)
references
References 17 publications
0
26
0
4
Order By: Relevance
“…However, the detection of CEC or DTC does not necessarily coincide with a poor outcome: Less than 50% of patients with known colorectal cancer metastasis were positive for CEC or DTC in peripheral blood as assessed by RT‐PCR for CK20 40. Also, in colorectal cancer patients staged N0 by routine pathohistology no difference in survival was detected between patients found CEC or DTC positive or negative in lymph nodes by immunohistochemistry for markers CK8/CK18 41…”
Section: Discussionmentioning
confidence: 99%
“…However, the detection of CEC or DTC does not necessarily coincide with a poor outcome: Less than 50% of patients with known colorectal cancer metastasis were positive for CEC or DTC in peripheral blood as assessed by RT‐PCR for CK20 40. Also, in colorectal cancer patients staged N0 by routine pathohistology no difference in survival was detected between patients found CEC or DTC positive or negative in lymph nodes by immunohistochemistry for markers CK8/CK18 41…”
Section: Discussionmentioning
confidence: 99%
“…CK20 mRNA has been detected in most of the primary colon tumours and liver metastases; however, the number of tested samples was low and a highly sensitive CK20 RT-PCR was used. 45 Another study showed that the CK20 protein is expressed, but that the mRNA is downregulated in colorectal tumour tissue compared with normal colon mucosa. 29 Our data on CK20 mRNA expression in 13 normal and 18 tumour samples support these results by showing a lower degree of CK20 mRNA expression in tumour tissue compared with normal mucosa (fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…[5253545556575859606162] Others report a lack of correlation between tumor seeding and clinical outcomes. [63646566]…”
Section: Miscellaneous Adverse Eventsmentioning
confidence: 99%